(untitled) (Marketing Journal, 2025)
This article presents a model for developing entrepreneurial competencies among students of engineering education programs. The analysis of entrepreneurial education models in foreign countries has been conducted, and their key characteristics have been examined. The proposed model aims to integrate technical knowledge with entrepreneurial skills and incorporates elem ents such as practical experience, mentorship, networking, and the development of communication abilities. 537